Analisis Kebutuhan Pengembangan Bahan Ajar IPA Terpadu Bermuatan Literasi Era Digital untuk Pembelajaran Siswa SMP Kelas VIII - Asrizal Asrizal; Festiyed Festiyed; Ramadhan Sumarmin (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Science learning should be able to develop the ability to think, to work, to use tools, and to live in the world for students. Integrated Science learning and integration of digital age literacy give good opportunities for students to develop fourth of these skills. But the reality shows that the implementa-tion of integrated science learning and integration of literacy in learning can’t be implemented well. An alternative solution of this problem is to develop integrated science learning by integrating digital age literacy. Before developing this integrated science materials it is necessary to conduct preliminary research as a basis for designing this learning materials. The purpose of this preliminary research is to describe the integration of knowledge basic competencies of science subjects, the implementation of integrated science learning, the learning materials available for science learning, and the integrating literacy of students. The type of research was descriptive research method. As object of the research consist of science teachers, syllabus and science learning materials, and students of grade VIII in ju-nior high school. Instruments to collect data consist of interview guide sheet, science syllabus and learning materials document, and digital age literacy test sheet. Research data was analyzed with de-scriptive statistic. Base on data analysis can be stated that results of this research are: 1). integrated science learning on grade VIII junior high school students can’t be implemented well, 2). the value of integration of science learning materials and its application in knowledge basic competence can be classified into enough category, 3). generally science learning materials in integrated science text-books and science worksheet on grade VIII junior high school are still separated form, and 4). the average value of digital age literacy of students is classified into low category.